Dissemination of the Urgency of Inheritance Law in Determining Inheritance Rights for Heirs in RW 08, Halim Perdanakusuma Subdistrict, Makassar District, East Jakarta City - Aria Caesar Kusuma Atmaja; Indah Sari; Ardison Asri; Selamat Lumban Gaol; Subhan Zein (Penerbit Jurnal Indonesia, 2026)
This study aims to enhance community understanding of inheritance law—covering civil, Islamic, and customary aspects—among residents of RW 08, Halim Perdanakusuma Subdistrict, Makassar District, East Jakarta. A qualitative descriptive approach was employed through observation, interviews, and documentation involving community members, local leaders, and legal practitioners. The program focused on structured and sustainable legal socialization to increase awareness of lawful inheritance distribution. The findings show that prior to the program, most residents relied on verbal agreements and family customs, leading to disputes and inequitable asset division. After the socialization activities, participants demonstrated improved comprehension of inheritance principles, recognized the importance of legal documentation, and showed greater willingness to consult legal experts. The study concludes that systematic legal education significantly enhances community literacy on inheritance law, promotes fairness in asset distribution, and helps prevent potential family conflicts. This initiative is recommended as a model for broader community-based legal empowerment programs in urban areas.